Gambaran Kebiasaan Cara Minum Tablet Fe Dan Kejadian Kecacingan Pada Ibu Hamil Yang Anemia - Sulistyaningsih, Dwi, Sulastri, S.Kp.,M.Kes, Dewi Suryandari, S.Kep., Ns (2015)
Anemia is very susceptible occured in pregnant women. Anemia in pregnant women called "Potential danger of mother and child". The effect of anemia is not good for the mother during pregnancy, childbirth, and also during the postpartum period. One of effort to reduce the incidence of anemia among pregnant women is Antenatal Care (ANC) where one of them by administering substances Fe. Basically, anemia caused by iron deficiency, but other than iron deficiency anemia is also caused by worm infections, malaria, tuberculosis and chronic lung disease. This research is aimed to describe anemia in pregnant women because of the habit of consuming manner Fe and helminthiases at the Puskesmas Kartasura. This research is descriptive quantitative research with cross sectional approach. The research populations were pregnant women in the working area Kartasura health centers who are anemic as many as 30 people. The sample of the research counted 30 pregnant women who are anemic by using total sampling technique. Collecting of the data using questionnaires and laboratory tests. The result of the research describes that the majority of pregnant women soffer from anemia aged 20-35 years is 21 respondent (70%), high school educated is 17 respondent (57%), third trimester of pregnancy is 19 respondent (63%), the second gravida of pregnancy is 22 respondent (73%), and the everage amount of Hb 9,33 g/dL. The research of examinations of pregnant women are anemia habit of consuming Fe tablets using tea water is 16 respondent (53%), and pregnant women who have helminthiases is 19 respondent (63%).Data were analyzed using univariate test. The research concluded that (1) the characteristic of the respondents were mostly 20-35 years old, high school education, the third trimester of pregnancy, and pregnancy number 2, and (2) a description of pregnant women with anemia in Puskesmas Kartasura largely consuming Fe tablet used tea water and suffered intestinal worms.